A study on consumers perception for green products: An empirical study from India (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The last three decades have seen a progressive increase in worldwide environmental consciousness due to rising evidence of environmental problems. Environmental protection is increasingly becoming a necessity and part of a bigger agenda in the urbanising world of developing countries. Given the increasing deterioration of the environment, India as a developing country need to prevent pollution and preserve its natural resources. Environmental attitudes constitute a significant part of environmental consciousness. Therefore, this paper empirically investigates the attitude of Indian consumers towards the environment in general. A survey was developed and administered across India. A total of 162 Indian consumers responded completed the questionnaire. The present paper made an attempt to understand the factor that influences environment conscious behaviour for green products. The finding of the study would help government to better understand consumers' environment conscious behaviour, for developing effective environmental policies required to reinforce green purchase. Moreover, companies will have insight about how to profile green consumers in India, to develop effective messages that will functionally and emotionally appeal to their target customers.